2014
DOI: 10.1017/langcog.2014.35
|View full text |Cite
|
Sign up to set email alerts
|

Languages adapt to their contextual niche

Abstract: It is well established that context plays a fundamental role in how we learn and use language. Here we explore how context links short-term language use with the long-term emergence of different types of language system. Using an iterated learning model of cultural transmission, the current study experimentally investigates the role of the communicative situation in which an utterance is produced (situational context) and how it influences the emergence of three types of linguistic systems: underspecified lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 80 publications
(113 citation statements)
references
References 191 publications
(317 reference statements)
9
103
1
Order By: Relevance
“…In this paper we present experimental evidence demonstrating that the degree of signal autonomy is causally related to contextual predictability: in an experiment where participants interact using an artificial language, highly predictable contexts favour systems composed of non-autonomous, contextdependent signals, whereas decreasing contextual predictability results in increased autonomy (context-independence). Crucially, we argue that these systems arise from the pressures of informativeness and simplicity (Regier et al, 2015;Kirby et al, 2015), with the degree of contextual predictability interacting 3 with these two pressures to restrict the space languages explore.…”
Section: Introductionmentioning
confidence: 93%
“…In this paper we present experimental evidence demonstrating that the degree of signal autonomy is causally related to contextual predictability: in an experiment where participants interact using an artificial language, highly predictable contexts favour systems composed of non-autonomous, contextdependent signals, whereas decreasing contextual predictability results in increased autonomy (context-independence). Crucially, we argue that these systems arise from the pressures of informativeness and simplicity (Regier et al, 2015;Kirby et al, 2015), with the degree of contextual predictability interacting 3 with these two pressures to restrict the space languages explore.…”
Section: Introductionmentioning
confidence: 93%
“…The domain of colors has been of particular interest to studies on language evolution ever since the classic work by Berlin and Kay (1969), and it has been proven to be useful as a reference space in pragmatic experiments as early as Krauss and Weinheimer (1967). Early results using the referential communication paradigm include the fact that the descriptions become shorter with increasing conversational history (Clark & Wilkes-Gibbs, 1986;Krauss & Weinheimer, 1964;Krauss & Weinheimer, 1966;Schober & Clark, 1989;Wilkes-Gibbs & Clark, 1992), but longer when referents are more similar (Krauss & Weinheimer, 1967) or when describing the referents for someone else as opposed to oneself (Fussell & Krauss, 1989). In these early studies, the intent of the research designs was to study linguistic communication in live interactions.…”
Section: Referential Communication Tasks and Interactionmentioning
confidence: 99%
“…Several studies have demonstrated that artificial languages will optimize to the semantic dimensions relevant in context. Through simulating iterated learning in experiments, defined as the “process in which an individual acquires a behavior by observing a similar behavior in another individual who acquired it in the same way” (Kirby, Cornish, & Smith, , p. 10681), artificial languages have been shown to develop: (a) underspecification with regard to irrelevant dimensions in a reference space (Silvey, Kirby, & Smith, ), (b) overspecification when relevant dimensions are difficult to discern (Tinits, Nölle, & Hartmann, ), and (c) either underspecified, holistic, or systematic linguistic structure depending on their contextual niche (Winters, Kirby, & Smith, ). These studies took the task's immediate perceptual context into account, but they did not manipulate the extent to which it was shared or not.…”
Section: Introductionmentioning
confidence: 99%
“…However, language is not merely a task of passively remembering and reproducing a set of constructions. Language is also a social and interactional phenomenon, whereby the role of usage, communication and coordination are salient pressures on the system (see also : Tomasello, 2008;Bybee, 2010;Winters, Kirby and Smith, 2014). This is the expressivity pressure.…”
Section: Solving the Problem Of Linkagementioning
confidence: 99%
“…These reuse strategies are evident in any situation where we observe ambiguity and are advantageous in communication systems skewed towards hearer inference over speaker effort (Levinson 2000). In short, when the context is known and informative, it is a useful resource in decreasing uncertainty about the intended meaning (Piantadosi et al 2012;Winters et al 2014). Employing a reuse strategy allows a population of speakers to make use of contextual relevance, and our powerful inferential capacities, to expand the expressivity of the system without detrimentally impacting upon our capacity to coordinate a linguistic system across a community of speakers.…”
Section: Division Of Labour In the Constructiconmentioning
confidence: 99%